2013
DOI: 10.5271/sjweh.3388
|View full text |Cite
|
Sign up to set email alerts
|

The association between long working hours and health: A systematic review of epidemiological evidence

Abstract: This is the first systematic review examining the association between long working hours and health after excluding differences in the definition of long working hours and the influence of shift work. We concluded that long working hours are associated with depression, anxiety, sleep, and coronary heart disease. Further studies dealing with long working hours and shift work appropriately are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
431
7
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 528 publications
(485 citation statements)
references
References 40 publications
30
431
7
17
Order By: Relevance
“…It is noteworthy that long WHs and shift work remained as significant associates with suicidal ideation after controlling possible confounders. Although long WHs more than 60 hours per week were well identified as a risk factor for suicidal ideation and other mental illnesses, as well, in prior research 11,12,21,22) , the association of shift work with suicidal ideation was identified in specific jobs such as police officers only 23) . Because the 2008 CHS was implemented nationwide, our analysis elucidated how shift work linked with suicidal ideation in all occupations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that long WHs and shift work remained as significant associates with suicidal ideation after controlling possible confounders. Although long WHs more than 60 hours per week were well identified as a risk factor for suicidal ideation and other mental illnesses, as well, in prior research 11,12,21,22) , the association of shift work with suicidal ideation was identified in specific jobs such as police officers only 23) . Because the 2008 CHS was implemented nationwide, our analysis elucidated how shift work linked with suicidal ideation in all occupations.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, by analyzing the relationship between long WHs and sleep duration, we found that those who worked over 60 hours per week had less than 5 hours of sleep daily, 1.8 times lower than those working 35−40 hours per week (data not shown). There is a meta-analysis study that concluded that sleep problem are related to mental health 11) . Furthermore, a prospective study showed that sleep disturbances are strong predictors of future depression 30) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although several reviews of this field exist (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), the few systematic quantifications of the evidence have been based on published cross-sectional (18,19,25) or published longitudinal studies (26). Given the potential publication bias in studies based on published data (27), an individual-participant metaanalysis of unpublished data would provide important complementary evidence to evaluate the effect of long working hours on mental health.…”
mentioning
confidence: 99%